Dental Stem Cells Harvested from Third Molars Combined with Bioactive Glass Can Induce Signs of Bone Formation In Vitro - Gregorio Raspini; Jan Wolff, Mika Helminen; Giovacchino Raspini; Mario Raspini; George K. Sándor (eJournal of Oral Maxillofacial Research, 2018)
Objectives: The aim of this study was to assess the interaction of a bioactive glass scaffold with cells derived from dental pulp, dental follicle and periodontal ligament.